1895 N.D. Rev. Codes 1289, Penal Code, ch. 40, § 7290 - (:unkn) unknown (General Publisher, 1895)
Every person who makes or keeps gunpowder, saltpeter, gun-cotton, nitroglycerine or dynamite or any compound of the same, or any fulminate or substance which is intended to be used by exploding or igniting the same, in order to produce a force to propel missiles or to rend apart substances, within any city, town or village, and any person who carries any of such explosives through the streets thereof, in any quantity or manner prohibited by law or by any ordinance, by law or regulation of said city, town or village, is guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER